Effect of electrolyte composition on rock salt surface degradation in NMC cathodes during high-voltage potentiostatic holds. (January 2019) - Tornheim, Adam; Sharifi-Asl, Soroosh; Garcia, Juan C.; Bareño, Javier; Iddir, Hakim; Shahbazian-Yassar, Reza; Zhang, Zhengcheng
Abstract: Surface degradation of lithium-ion cathodes at high voltages represents a significant barrier to increasing the useable energy of conventional cathodes. Though much work has been focused on mitigating the detrimental effects of such phenomena, the complex and correlated mechanisms involved have made progress difficult. Herein, the effect of electrolyte identity on surface degradation is examined. LiNi0.5 Mn0.3 Co0.2 O2 (NMC532)/Li4 Ti5 O12 (LTO) full cells were constructed using three different electrolytes: a baseline organic carbonate electrolyte, a baseline organic carbonate electrolyte with an oxidizable additive, and a fluorinated carbonate electrolyte. Each system was subjected to a 60 h potentiostatic hold at 3.05 V (4.6 V vs. Li + /Li) and subsequently deconstructed for characterization via transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS). Molecular simulations were carried out on each distinct component of the three electrolytes in contact with crystal surfaces of an NMC532 particle. Results indicate an affinity for the additive-containing electrolyte to extract atomic oxygen from the cathode surface, whereas the fluorinated electrolyte components have negligible interactions. Hydrogen abstraction from the baseline electrolyte is facilitated by the NMC532 surface. TEM analysis of cathode surfaces, after the potentiostatic holds, revealed that the NMC532 particles cycled with the additive-containing electrolyte underwent significant surface degradation, including changes to local crystal structure in a region penetrating 20–40 nm from the surface; consistent with oxygen and lithium loss from the cathode material. However, the NMC532 in contact with the fluorinated electrolyte showed a disordered layer of just a few nm in thickness, similar to the depth of crystal disorder observed in pristine NMC532 primary particles. EELS data of the oxygen K-edge also indicated transition metal (TM) reduction, consistent with oxygen loss and changes in crystal structure extending into the cathode surface for each of the electrolytes surveyed. These surface reactions, including oxygen loss, are shown to correlate well with elevated oxidation currents and surface reconstructions of cathode particles. Graphical abstract: fx1 Highlights: Fluorinated electrolyte solvent molecules do not interact with the cathode surface. An oxidizable additive removes oxygen from the cathode surface, causing damage. Oxygen loss leads to surface reconstruction and parasitic currents at high voltage. Degree of oxygen loss at high voltage depends on electrolyte identity.